Association between perception of esthetics and oral health related quality of life among adolescents in the Eastern Province, Saudi Arabia - Deamah Aleisa; Tasneem Alluhaidan; Muneera Almedaires; Alhanouf Albarrak; Zainah Salloot; Bayan Alshuhail; Maha ElTantawi; Khalifa Alkhalifa; Muhammad Nazir (Elsevier, 2019)
Aim: This study aimed to investigate the association of perception of esthetics with oral health related quality of life (OHRQoL) among adolescents in the Eastern Province of Saudi Arabia. Methods: A cross-sectional study was conducted in the Eastern Province of Saudi Arabia in 2018. It included 1638 participants from public schools stratified by gender and randomly selected using cluster sampling. Students were included if they were 11-18 years old, with no disabilities and had parental consent. Data was collected about participants' gender and age. Perception of oral esthetics (exposure) was measured by the Oro-Facial Esthetic Scale (OES-AR). The OHRQoL (outcome) was assessed using the Child Oral Health Impact Profile- short form (COHIP-SF19). Results: The response rate was 99.7%. The mean (SD) of the participants was 14.5 (1.6) and males constituted 48.4%. The mean esthetic score was 31.44 (SD = 5), and mean OHRQoL score was 20.21 (SD = 11.8). The esthetic score was significantly higher in females (mean = 32.2) than males (mean = 30.6, P < 0.0001). The OHRQoL score was negatively correlated with the perception of esthetics (r = −0.23, P = 0.13). Conclusion: Esthetic score was higher among females, and inversely related to OHRQoL scores.